Catfish Culture Techniques with Aquaponic Systems in the Elderly Group as an Effort to Increase Productivity and Economic Independence of the Community in Pakal District, Surabaya - Putri Desi Wulan Sari; Daruti Dinda Nindarwi; Lalu Aldy Kurnia Aji; Mada Dewantara (Kontribusia : Research Dissemination for Community Development, 2023)
Fish farming is an activity to maintain fish in a controlled environment for a certain period to get results with a certain value. Fish farming activities can be carried out on a household production scale, by modifying science and technology so that it becomes an activity that can be carried out by various levels of society. Catfish (Clarias sp.) is one of the most widely used fishery commodities by people who carry out fish farming activities on a household scale. In addition to its delicious and savory taste, catfish is not susceptible to disease, so it is easy to culture on a household scale. In line with the need for community economic independence, food security, and community productivity in utilizing the potential of existing resources, assistance for catfish farming activities is carried out in the elderly group in Pakal sub-district, Surabaya.